Quem não sonhou em ser um jogador de futebol?: trabalho com projetos para reelaborar foregrounds - Biotto Filho, Denival [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The concept of foreground relates to how individuals see their future, including their wishes, dreams, intentions, expectations, hopes, fears, and obstacles. The concept of foreground is usually discussed from a social perspective, and includes the social, political and economic context of a person. The reasons that students have for learning are formed from their foregrounds therefore, students with ruined foregrounds feel they have no real prospects for the future and no reason to learn. Although there are studies that discuss the relation between the foreground of individuals and their engagement in educational activities, this research does not discuss what to do when a student's foreground does not offer any real reasons for learning. This leads to my research question: how to reform foregrounds in educational settings? To investigate this subject, I chose to develop a set of activities with a group of school children in an educational setting, which would allow me to understand how such activities could contribute to reforming their foregrounds. This data collection was set in a social institution that shelters economically poor children and adolescents in an after-school center. The theme of this project was Soccer Project, which focused on the natural desire of many children to become soccer players. Included, were activities based on the project work proposal, which included games, chats with professional guests, interviews, acting, and recording and editing video. Interviews with youth participants and episodes from the Soccer Project were analyzed to identify possible reforms in their future, as well as to discuss the concept of foreground in general. The data analysis took into account the following research objective: to investigate the student's foregrounds in an educational setting based on project work proposals, in order to discuss the foreground reforms. This research will contribute in the following ways: to the...

O conceito de foreground se refere a como uma pessoa vê seu próprio futuro. Envolve seus desejos, sonhos, intenções, expectativas, esperanças, medos e obstáculos. Este conceito é discutido em uma perspectiva social e inclui o contexto social, político e econômico do indivíduo. Os motivos para alguém aprender são formados em seu foreground e, consequentemente, alunos com foregrounds arruinados, sem perspectivas atraentes de futuro, têm poucos motivos para aprender. Apesar de haver pesquisas que apresentam importantes contribuições para as relações entre o foreground de um indivíduo e seu engajamento em atividades educativas, elas não discutem o que pode ser feito quando o foreground de um estudante não oferece motivos para a aprendizagem. Isso remete à minha pergunta de pesquisa: como reelaborar foregrounds em ambientes educacionais? Para investigar o pretendido, optei por desenvolver um conjunto de atividades em um ambiente educacional com um grupo de jovens em idade escolar para entender de que forma tais atividades poderiam contribuir para a reelaboração de seus foregrounds. Este cenário da coleta de dados foi configurado em uma instituição social de semiabrigo e intitulado Projeto Futebol. Esse tema foi explorado tendo como foco o desejo de muitas crianças de se tornarem jogadores de futebol. As atividades desenvolvidas foram baseadas na proposta de trabalho com projetos e envolveram jogos, conversas com profissionais convidados, entrevistas, produção de maquete, gravação e edição de vídeo. Entrevistas realizadas com os jovens participantes e episódios ocorridos durante o Projeto Futebol foram analisados para identificar possíveis reelaborações em suas perspectivas de futuro e para discutir o próprio conceito de foreground. A análise dos dados levou em conta o seguinte objetivo de pesquisa: investigar os foregrounds de estudantes em um ambiente educacional baseado na proposta pedagógica de trabalho com...
Keywords: Mathematics - Philosophy; Matemática - Filosofia; Motivação (Psicologia); Psicologia da aprendizagem; Exclusão social; Metas (Psicologia); Matemática - Estudo e ensino; Futebol